THE INFLUENCE OF ENTREPRENEURIAL EDUCATION, SELF EFFICACY, LOCUS OF CONTROL, ON THE ENTREPRENEURSHIP INTENTIONS OF SMKN 3 JAKARTA STUDENTS - Shah, Azmi Auliya; Eryanto, Henry; Munawaroh (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study was conducted to determine the effect of entrepreneurship education, self-efficacy, locus ofcontrol, on the entrepreneurial intentions of students at SMK Negeri 3 Jakarta. The research wasconducted by survey research method with a sample of 191 students and using proportional randomsampling technique. In collecting data, researchers used a questionnaire and analyzed using multiplelinear regression techniques to test the validity and reliability. From the results of the research that hasbeen carried out, it shows that entrepreneurship education, self-efficacy, locus of control onentrepreneurial intentions among students. Therefore, teachers in the school environment arerequired to encourage entrepreneurship education, self-efficacy, locus of control, towards entrepreneurialintentions through various programs and entrepreneurship education to increase and explorestudents' entrepreneurial intentions.